The Language(s) of the Diaries - Svoboda, Joseph Mathia (Newbook Digital Texts, 2016)
A journal of commercial voyages and domestic life on the Tigris River -- the language used in the diaries.
jms_000_00_050_ser_lan
Keywords: 19th century; Baghdad; Basrah; Commerce; Iraq; Ottoman empire; Lynch brothers; Middle East; Tigris; Travel journal; Svoboda